Periprosthetic hip infections caused by : a rare case report and literature review - Jun Wei Feng; Peng Hao; Jiang Hu; Xia Deng; Yue Wang (Journal of International Medical Research, 2024)
Periprosthetic hip infection caused by Brucella abortus is rare and only a few cases have been reported. This current case report presents a case of a man in his early 50s who developed periprosthetic hip infection 2 years after right hip arthroplasty. There was no fever or pain, the usual cardinal signs of infection, except for a sinus tract at the previous surgical incision. Laboratory and arthrocentesis culture examinations (done twice) confirmed infection with B. abortus . Accordingly, a two-stage revision surgery was performed accompanied by antibiotic treatment with doxycycline and rifampicin after each stage. There was no recurrence at the 2-year follow-up, with good functional recovery of the hip joint. Clinically, this case serves to highlight the fact that periprosthetic hip infections caused by B. abortus might not present with the typical symptoms such as fever or hip pain. Furthermore, this current case involved a chronic sinus tract, so the diagnostic and therapeutic course of this case offers useful insights for managing similar cases in the future. In addition, a review of the literature on the diagnosis and treatment of Brucella -caused periprosthetic hip infection is presented.